Searching new structural scaffolds for BRAF inhibitors. An integrative study using theoretical and experimental techniques - Campos, Ludmila E; Garibotto, Francisco M; Angelina, Emilio; Kos, Jiri; Tomašič, Tihomir; Zidar, Nace; Kikelj, Danijel; Gonec, Tomas; Marvanova, Pavlina; Mokry, Petr; Jampilek, Josef; Alvarez, Sergio E; et al. (Bioorganic chemistry, 2019)
The identification of the V600E activating mutation in the protein kinase BRAF in around 50% of melanoma patients has driven the development of highly potent small inhibitors (BRAFi) of the mutated protein. To date, Dabrafenib and Vemurafenib, two specific BRAFi, have been clinically approved for the treatment of metastatic melanoma. Unfortunately, after the initial response, tumors become resistant and patients develop a progressive and lethal disease, making imperative the development of new therapeutic options. The main objective of this work was to find new BRAF inhibitors with different structural scaffolds than those of the known inhibitors. Our study was carried out in different stages; in the first step we performed a virtual screening that allowed us to identify potential new inhibitors. In the second step, we synthesized and tested the inhibitory activity of the novel compounds founded. Finally, we conducted a molecular modelling study that allowed us to understand interactions at the molecular level that stabilize the formation of the different molecular complexes. Our theoretical and experimental study allowed the identification of four new structural scaffolds, which could be used as starting structures for the design and development of new inhibitors of BRAF. Our experimental data indicate that the most active compounds reduced significantly ERK½ phosphorylation, a measure of BRAF inhibition, and cell viability. Thus, from our theoretical and experimental results, we propose new substituted hydroxynaphthalenecarboxamides, N-(hetero)aryl-piperazinylhydroxyalkylphenylcarbamates, substituted piperazinylethanols and substituted piperazinylpropandiols as initial structures for the development of new inhibitors for BRAF. Moreover, by performing QTAIM analysis, we are able to describe in detail the molecular interactions that stabilize the different Ligand-Receptor complexes. Such analysis indicates which portion of the different molecules must be changed in order to obtain an increase in the binding affinity of these new ligands.
Keywords: Synthesis; inhibitory proteinkinas; Cell Line, Tumor; screeningové testy protinádorových léčiv; simulace molekulového dockingu; vazba proteinů; Molecular Structure; Bioassays; lidé; Antineoplastic Agents; protinádorové látky; molekulární struktura; Proto-Oncogene Proteins B-raf; protoonkogenní proteiny B-Raf; Protein Kinase Inhibitors; Drug Screening Assays, Antitumor; Molecular modeling; Virtual screening; vemurafenib; Vemurafenib; Protein Binding; Molecular Docking Simulation; nádorové buněčné linie; BRAF inhibitors; Humans